Middle Aortic Syndrome: Pathogenesis, Visceral Manifestations, and Management - Monroe, Eric J.; Morray, Brian H.; Zhao, Yongdong; Smith, Caitlin A. (Digestive Disease Interventions, 2018)
Middle aortic syndrome (MAS) is characterized by severe narrowing of the abdominal aorta, frequently involving the great abdominal vessels. Although increasingly implicated in primary hypertension, up to one-third of cases affect the mesenteric vasculature, and the resultant manifestations may be underrecognized. Early intervention with interdisciplinary medical management and invasive arterial reconstruction affords preservation of end-organ function and improvement in patient survival. This article reviews the embryology of the thoracoabdominal aorta and major abdominal arteries, as well as the pathogenesis, clinical manifestations, and management of the nonatherosclerotic abdominal coarctation otherwise known as MAS.
Keywords: middle aortic syndrome; visceral manifestations; pathogenesis